PENGELOLAAN OBJEK WISATA ACEH JAYA: HARAPAN DAN KENYATAAN DALAM PENINGKATAN EKONOMI MASYARAKAT - Marjulita Marjulita; Alimas Jonsa; Ikhsan Ikhsan (Jurnal Community, 2019)
This paper will review the tourism management in Aceh Jaya Regency, analyzing reality and expectations. The tourism management; can theoretically improve the economy of the community, with the potential of natural resources owned. Qualitative was chosen as the method used in retrieving and analyzing data in this paper. Based on the results of research and analysis of data found by the author Aceh Jaya attractions are very potential with the natural beauty that is owned, has a very complete tourist attraction starting from a very beautiful beach, a very beautiful mountains and waterfalls that are very tempting but all the potential it has not yet had an impact on improving people's welfare. This happens because there is still a lack of promotion and the available facilities cannot be functioned and there is no collaboration between the government and entrepreneurs in the management of attractions so that it is increasingly difficult to achieve expectations in the professional management of attractions.